User Acceptance of Haulage WAP Based Enquiry - Asmah, Ahmad (2008)
With rapid growth in development of mobile technology has been found useful in logistic industry. It is widely used in tourism, museum guides, shopping guides, ticket booking, e-learning etc. However the potential of mobile service for haulage business is difficult to estimate in prior because hardly any user acceptance can be test without carry any implementation of the application. Prototyping is an approach that is not implements full functionality application. Therefore this study was conducted to use prototyping into the development process in order to be able test on the early user acceptance in a real context. This approach can save money and time and also increase in productivity and quality of the application development.